Comparison of biofouling on 3D-printing materials in the marine environment. (October 2021) - Ryley, Matthew; Carve, Megan; Piola, Richard; Scardino, Andrew J.; Shimeta, Jeff
Abstract: 3D printing has an increasing variety of applications in the marine environment for customized or replaceable components of instrumentation and infrastructure. Because marine biofouling can interfere with the performance of such applications and plays an important role in species dispersal, there is a need to understand biofouling dynamics on the materials used. This study compared biofouling on common 3D-printing polymers printed by common methods - polycaprolactone (PCL) printed by fused deposition modelling, VisiJet® SL Clear printed by stereolithography, and VeroClear™ printed by PolyJet, as well as the comparison materials polydimethylsiloxane (PDMS, used in many experimental biofouling studies) and glass - and related fouling to material properties. Bacterial assemblages in 2- and 4-week old biofilms were similar on all materials, dominated by cyanobacteria and proteobacteria. The extent of macrofouling after 12 weeks differed significantly among materials, with the greatest coverage on glass (98.4%) and the least on PCL (86.8%). Macrofouler assemblages differed significantly, with 3D-printing polymers generally having less microalgae and more encrusting bryozoans than PDMS and glass. PCL was the most extreme of the 3D-printing materials in having the least microalgae and most bryozoans (arborescent and encrusting combined). Macrofouling coverage was not significantly related to material hydrophobicity, elastic modulus, hardness, or roughness. In contrast, macrofouler assemblage structure had a statistically significant relationship to hardness and a marginally significant relationship to hydrophobicity (explaining 19.0% and 8.6% of the variation in the assemblages, respectively). The reduced biofouling coverage and altered species composition on PCL may be advantageous for using PCL in marine applications of 3D printing, although other factors should be considered such as material degradation over time. Highlights: 3D printing has an increasing variety of applications in the marine environment. Biofouling coverage & composition differed among 3D-printing and comparison materials. Biofouling composition was related to physical material properties. Polycaprolactone has advantages for use in marine applications of 3D printing.